(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2024)
Scalable blockchain architectures are essential for enabling high-throughput decentralised applications (dApps) that require transaction processing rates exceeding the capabilities of first-generation blockchain platforms. Ethereum mainnet processes approximately 15-30 transactions per second (TPS), while enterprise and DeFi applications demand 10,000-100,000 TPS with sub-second finality. This paper proposes the Scalable Blockchain Architecture Framework (SBAF), a systematic evaluation of five scaling architectures – Layer-2 rollups (optimistic and zk-rollups), sharding, parallel execution chains, modular blockchain stacks, and DAG-based consensus – across four dApp performance categories: DeFi trading platforms, supply chain provenance systems, decentralised social networks, and NFT marketplaces. SBAF introduces the Scalability-Decentralisation Quality Score (SDQS) integrating throughput, finality latency, decentralisation preservation, and security guarantee strength. Key results: zk-rollups achieve the highest SDQS (0.912) balancing throughput (4,000+ TPS) with strong security inheritance from Layer-1; modular stacks achieve the highest raw throughput (50,000+ TPS) but lower decentralisation; sharding achieves the best native Layer-1 scaling (1,000+ TPS) without off-chain trust assumptions. The framework provides architecture selection guidance for dApp developers and blockchain protocol designers.